Serdemetan antagonizes the Mdm2-HIF1α axis leading to decreased levels of glycolytic enzymes. - Jason A Lehman; Paula M Hauck; Jaimie M Gendron; Christopher N Batuello; Jacob A Eitel; Allan Albig; Madhavi P Kadakia; Lindsey D Mayo (PLoS ONE, 2013)
Serdemetan (JNJ-26854165), an antagonist to Mdm2, was anticipated to promote the activation of p53. While regulation of p53 by Mdm2 is important, Mdm2 also regulates numerous proteins involved in diverse cellular functions. We investigated if Serdemetan would alter the Mdm2-HIF1α axis and affect cell survival in human glioblastoma cells independently of p53. Treatment of cells with Serdemetan under hypoxia resulted in a decrease in HIF1α levels. HIF1α downstream targets, VEGF and the glycolytic enzymes (enolase, phosphoglycerate kinase1/2, and glucose transporter 1), were all decreased in response to Serdemetan. The involvement of Mdm2 in regulating gene expression of glycolytic enzymes raises the possibility of side effects associated with therapeutically targeting Mdm2.